'Does compliance with BOAST guidelines matter for displaced supracondylar fractures in children?': the experience of a tertiary referral major trauma centre over a 3.5-year period. Issue 2 (17th July 2020) - Tzatzairis, Themistoklis; Firth, Gregory; Loke, Wei Jie; Serlis, Athanasios; Ramachandran, Manoj
Abstract : Supracondylar fractures are the most frequently occurring paediatric fractures about the elbow and can be associated with neurovascular injury. For that reason, the British Orthopaedic Association has published the British Orthopaedic Association Standards for Trauma (BOAST) 11 guidelines, aiming to the best management of supracondylar fractures. The aim of this study was to assess adherence to the BOAST 11 guidelines for displaced supracondylar fractures at a Major Trauma Centre in London, UK between 2015 and 2018 and to see whether adherence to guidelines affected the outcomes. A retrospective review was carried out between January 2015 and August 2018 of all paediatric patients who underwent either closed reduction and percutaneous pinning or open reduction and fixation for a displaced supracondylar fracture of the humerus. One hundred nine patients between 1 and 16 years of age with isolated displaced extension type supracondylar fractures (Gartland II, III and IV) were included in the study. The current study did not manage to achieve complete compliance with the BOAST 11 guidelines. K-wire size, fixation technique and pre-, intra-, postoperative documentation were the most important points of lack of compliance. However, deviating from specific guidelines did not cause any adverse clinical outcomes. Lack of correct documentation either preoperatively or postoperatively could be detrimental to patient outcome, especially with respect to neurovascular status. Implementation of a clerking template for use in the electronic medical records for all children with displaced supracondylar fractures is of value in order to improve our documentation.